ADAPTATION OF LANGUAGE CODE "SPEECH CODE" IN INTER-CULTURAL COMMUNICATION IN LOCAL RESIDENTS AND INVADERS IN BEDAHAN VILLAGE SAWANGAN DEPOK - Sri Rejeki Sulistiyowati; Nani Nurani Muksin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
Humans always communicate in their lives, because humans need communication to interact with other humans. The communication process has a lot of elements so that what is conveyed by the communicator can be conveyed clearly to the communicant. Intercultural communication is communication carried out by people who have different cultural backgrounds that have been adopted since ancient times until now. Communication occurs through verbal and non-verbal messages that occur among humans as social creatures supported by the surrounding environment. The purpose of this study is to examine the process of Speech Code adjustment in intercultural communication, especially those that occur in Javanese who interact with Betawi people in Bedahan village, Sawangan, Depok. The research method used in the study is a qualitative method with a qualitative descriptive approach and data collection techniques using observation, interview, and documentation techniques. The results of this study indicate that the cultural adaptation experienced by immigrants to indigenous people in Bedahan Sawangan Depok village tends to use adaptation in language code and cultural acculturation. Language codes that can be adapted are dialect language codes and gestures. While cross-cultural adaptation that develops in immigrant residents is acculturation adaptation where immigrants want to learn some of the host culture's behavior, beliefs and values without releasing their original cultural behavior, beliefs and values of the immigrant residents.